The Educational Value of Contextual Sufism in Kaca Benggala Films - Agus Sholikhin; Rohmaniyah, Naila; Siti Wulan Asih; Ahmad Yaim; Sugiyanto; Muhib Ali Hasan Ristia (International Journal of Post Axial: Futuristic Teaching and Learning, 2023)
This reseach aims to explain the educational value of Sufism contextual in the film Kaca Benggala. The researchers used content analysis and interviews to obtain information of the content Kaca Benggala film. There are two contextual values ​​of Sufism educational in the film Kaca Benggala as follows; the first, the value of takhliatul qolbi (puring the heart from reprehensible traits), someone who does not have a pure heart and commits a disgraceful act, then they will receive recompense and destruction, therefore someone who has a clean heart and stay away from despicable acts they will get mercy from Allah SWT. Second, the value of tahliatul qolbi (heart with dzikrullah), someone who has a pure heart and riyadhah will receive grace from Allah SWT and will be elevated in rank both in the life of the world and the hereafter. The values ​​of contextual Sufism educational in the film Kaca Benggala can be a reflection of education today, considering that in the modern era many people are greedy, arrogant and revengeful towards others.